If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6w+2(w+2)=10
We move all terms to the left:
6w+2(w+2)-(10)=0
We multiply parentheses
6w+2w+4-10=0
We add all the numbers together, and all the variables
8w-6=0
We move all terms containing w to the left, all other terms to the right
8w=6
w=6/8
w=3/4
| n−772=8 | | C(x)=11+.20(40) | | 24+4x=48-23 | | 88.36=6.3(x+6)+0.1x | | 3/4j-6=-18 | | 2.8x+12=-1.4-9 | | 2(7.5)=16-y | | -16n-23.3=16.99-56.29 | | 6x-18=4x+18 | | 14+(-6/5)x=-7 | | (2x+4/5)(4x-3/7)=0 | | v3+ 14=16 | | (-5)/(2/3)=x | | -2=v-20 | | -5k+7=-13 | | 3^2x+1=82 | | 14+-6/5x=-7 | | 32x+1=82 | | -25=m-10 | | 8x+4=42-48 | | 5(x+10)=7x+2x-20 | | 8a+16=4a | | 3x^2+4x=320 | | P=11(6x15) | | 25x-10x+430=P | | -8(3x+8)=2(x-6) | | 11(6x15)=x | | 13x-(5×-11)=-13 | | 8.7x+4.63=-11.3x+3.41 | | (2n+4)+(n-2)= | | P=25x-10x+430 | | 6z-9=5(z+2) |